Aplastic crisis in a child with hereditary spherocytosis with a strong family history resolving with supportive care - M. D., Balaji; Vinay, Vadlamudy; V., Shankar Vangalpudi (International Journal of Contemporary Pediatrics, 2018)
Hereditary spherocytosis (HS) is a familial hemolytic disorder with marked heterogeneity. Clinical features range from asymptomatic to fulminant hemolytic anaemia. The Human Parvovirus Virus B19 induced aplastic crisis can unmask several hereditary hematological disorders that have been normally compensated. Among these conditions, hereditary spherocytosis has been extensively reported. The clinical importance of this report is that in the case of an abrupt onset of unexplained severe anemia and jaundice, one should consider underlying hemolytic anemias mostly hereditary spherocytosis complicated by HPV B19 aplastic crisis. We herein report a 13-year-old boy who is a known case of hereditary spherocytosis presented with severe pallor, jaundice and pancytopenia after a febrile illness.